Deloading tape reduces muscle stress at rest and during contraction - Hug, F.; Ouellette, A.; Vicenzino, B.; Hodges, P. W.; Tucker, K. (Medicine & Science in Sports & Exercise, 2014)
Purpose: Taping techniques that aim to protect and reduce stress on an injured tissue during rehabilitation are common in sport. Called deloading tape, the mechanism of action is hypothesized to involve effects ranging from direct mechanical deloading of the underlying soft tissues to psychological effects on confidence. There is no evidence that deloading tape has direct mechanical effects. This study used an elastographic technique (supersonic shear imaging) to test the hypothesis that deloading tape applied to the skin over the rectus femoris would reduce stress within the taped area of this muscle.